In vitro regeneration of Acacia crassicarpa A. Cunn Ex benth through organogenesis from juvenile sources - Akeng, Griffin; Muniandi, Sures Kumar; Ab Shukor, Nor Aini (WFL Publisher, 2014)
Micropropagation through tissue culture technique offers an alternative to traditional vegetative propagation to mass propagate selected trees for large-scale forest plantation. Therefore, this study aimed to develop a protocol for the micropropagation of A. crassicarpa. Nodal stem segment and leaf obtained from 2 month-old aseptically germinated seedlings were used as explant in this study. Nodal stem segment was found to be the most appropriate explant for shoot formation when cultured on a MS medium supplemented with 6-benzylaminopurine (BAP). The highest mean number of shoots (5) and the longest mean shoot elongation (8 mm) occurred on a medium supplemented with 0.5 mg l-1 BAP. The longest mean shoot length (8 mm) and the highest mean number of explants per culture (7) were obtained on medium without any plant growth regulator. When cultured on a medium supplemented with 2,4-dichlorophenoxy acetic acid (2,4-D), nodal stem segment explant developed roots and callus (after 14 days). The highest mean number of roots (8.3 = 8) and the longest mean root length (12.0 = 12 mm) were obtained from the medium supplemented with 10.0 and 2.0 mg l-1 2,4-D, respectively. The highest mean number of roots (20.6 = 21) and the longest mean root length (10.4 = 10 mm) were obtained from the medium supplemented with 10.0 and 2.0 mgl-1 2,4-D, respectively, while the highest intensity of callus was produced on a medium supplemented with 8.0 and 10.0 mg l-1 2,4-D, and which was only able to produce root without any shoot formation. The calli produced were compact, watery and white in colour. Survival rate of plantlets was higher (100%) when transferred into the autoclaved mixture of soil, sand and peat (3:3:1) than those transplanted in an unautoclaved soil mixture (6.6%). Survival percentages of the plantlets in the culture room and greenhouse condition were 85 and 100%, respectively.